PROSPECTS OF THE APPLICATION OF SUPRAMOLECULAR GELS IN EXPERIMENTAL SURGERY - Timur M. Valiev; Margarita B. Petrova; Evgeny M. Mokhov (Кубанский научный медицинский вестник, 2019)
Aim. To analyse the effect of supramolecular gels on the healing of experimental wounds using the approaches of problem-critical analysis. Materials. 29 Russian and foreign publications indexed in RSCI (E-library, “Advanced Search” mode), Scopus (“Article title, abstracts, keywords”), Web of Science (basic mode), PubMed (basic search mode), Cochrane (“Article title, abstracts, keywords” mode) databases were analysed. Results. Generalization of literature data published on the application of supramolecular gels under analysis for wound regeneration and repair was carried out. Conclusion. Damage to the skin and deeper tissues is an urgent medical problem, which leads to a constant search for means to stimulate the regeneration of wounds. Supramolecular gels are promising compounds, which can be different in terms of chemical composition. These compounds can form and break down under the inﬂuence of various chemical and physical factors. Important properties of supramolecular gels involve the ability to perform the transport function for the delivery of biologically active substances to the tissues, as well as their antibacterial effect and wound-healing properties.